1982
DOI: 10.1051/rnd:19820402
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fertilization after initiation of sperm motility in the hamster epididymis

Abstract: Summary. Hamster spermatozoa, collected from the caput and the cauda of the epididymis, are known to differ in their motility. They do not normally acquire fertilizing ability until they reach the proximal portion of the cauda epididymidis. The aim of the present investigation was to test the fertilizing capacity of spermatozoa from the caput epididymis after initiation. Sperm cells were incubated by adding 10 mM caffeine and 20-30 p. 100 epididymal plasma to the culture medium. Superovulated females were inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…A report published earlier showed that when the uteri of superovulated female hamsters were inseminated with caput or cauda spermatozoa, caput spermatozoa failed to fertilize eggs, whereas cauda spermatozoa achieved 88% success [20]. Clinical data also suggest that pregnancy outcomes after cauda epididymal anastomoses are superior to those after caput anastomoses [22]. Given this information, we were not surprised to find that, in our group, the majority (95%) of patency cases undergoing LIVE at the cauda had PMS in their ejaculate, and the percentage of PMS was relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…A report published earlier showed that when the uteri of superovulated female hamsters were inseminated with caput or cauda spermatozoa, caput spermatozoa failed to fertilize eggs, whereas cauda spermatozoa achieved 88% success [20]. Clinical data also suggest that pregnancy outcomes after cauda epididymal anastomoses are superior to those after caput anastomoses [22]. Given this information, we were not surprised to find that, in our group, the majority (95%) of patency cases undergoing LIVE at the cauda had PMS in their ejaculate, and the percentage of PMS was relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate changes in the outer dense fibres but the factors controhng this are not known. Circular motion, while demonstrated to be incompatible with transport through the uterotubal junction in rats (Gaddum-Rosse, 1981) and hamsters (Kann &Raynaud, 1982), and presumably so in the mouse (Pavlok, 1974), does permit fusion with the vitellus in sub-zonal insemination in mice (Lacham & Trounson, 1991). A change in flagellar stiffness, possibly related to oxidation of disulphide bridges in the outer dense fibres, may bring about the forward progression seen in spermatozoa on maturation, as observed in the ham- istributions of values of three derived ster (Cornwall ef al., 1986;Yeung et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The anticipated rapid postejaculatory changes are in marked contrast to responses of somatic cells, where the need for RVD rarely arises (O'Neill, 1999). Kann and Raynaud (1982) demonstrated that hamster caput sperm, stimulated to motility by caffeine, failed to fertilize eggs when inseminated into the uterus and exhibited angulated flagella (reflecting the swollen state). However, 22% of eggs were fertilized when sperm were pretreated with forward motility protein to prevent flagellar angulation.…”
Section: Importance Of Volume Regulationmentioning
confidence: 97%